A Multistep, Consensus‐Based Approach to Organ Allocation in Liver Transplantation: Toward a "Blended Principle Model". Issue 10 (14th August 2015) - Cillo, U.; Burra, P.; Mazzaferro, V.; Belli, L.; Pinna, A. D.; Spada, M.; Nanni Costa, A.; Toniutto, P.; ,
Abstract : Since Italian liver allocation policy was last revised (in 2012), relevant critical issues and conceptual advances have emerged, calling for significant improvements. We report the results of a national consensus conference process, promoted by the Italian College of Liver Transplant Surgeons (for the Italian Society for Organ Transplantation) and the Italian Association for the Study of the Liver, to review the best indicators for orienting organ allocation policies based on principles of urgency, utility, and transplant benefit in the light of current scientific evidence. MELD exceptions and hepatocellular carcinoma were analyzed to construct a transplantation priority algorithm, given the inequity of a purely MELD‐based system for governing organ allocation. Working groups of transplant surgeons and hepatologists prepared a list of statements for each topic, scoring their quality of evidence and strength of recommendation using the Centers for Disease Control grading system. A jury of Italian transplant surgeons, hepatologists, intensivists, infectious disease specialists, epidemiologists, representatives of patients' associations and organ‐sharing organizations, transplant coordinators, and ethicists voted on and validated the proposed statements. After carefully reviewing the statements, a critical proposal for revising Italy's current liver allocation policy was prepared jointly by transplant surgeons and hepatologists. Abstract : The authors present a critical proposal for the implementation of the current liver allocation policy in Italy developed following the results of a national Consensus Conference process aimed to revise, on the basis of scientific evidence, the best indicators for guiding organ allocation policies in the urgency, utility, and benefit models. See the editorial from Berg on page2537 .